Long-term risk of cardiovascular and cerebrovascular disease in women with a personal history of placental abruption - Lozada Martínez, Ivan David (2022)
Maternal and perinatal health is one of today’s global health priorities. Cardiovascular disease and stroke are the leading causes of maternal mortality. Placental abruption remains a critical concern for maternal morbidity because it has been associated with long-term vascular disease. However, there is neither much literature available in Spanish nor recent evidence elucidating some questions on this topic. Thus, this review aims to synthesize recent evidence on the long-term risk of cardiovascular and cerebrovascular disease in women with a personal history of placental abruption. It was found that, through complex pathophysiological mechanisms involving the structure and functionality of the placental vascular network with subsequent extension of vascular injury and production of proinflammatory and procoagulant factors which remain after delivery, major cardiovascular events are precipitated in the medium and long term. High-quality evidence has shown that the risk of maternal complications in women with placental abruption accounts for 2.14, rising even higher for those with severe placental abruption. In the medium and long term, the mortality risk caused by coronary heart diseases is 2.64 and by cerebrovascular disorders is 1.70, with equal risk for both ischemic and hemorrhagic strokes. It can therefore be concluded that cardiovascular and cerebrovascular risk is imminent in women with a history of placental abruption due to a number of vascular pathophysiological mechanisms. However, this risk is considerably increased when associated with traditional and non-traditional modifiable factors.